HUBUNGAN STATUS GIZI DAN ASUPAN ENERGI DENGAN KELELAHAN KERJA PADA PEKERJA DI PT. PERKEBUNAN NUSANTARA I PABRIK KELAPA SAWIT PULAU TIGA TAHUN 2015 - daniel tasmi; halinda sari lubis; eka lestari mahyuni (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACTThe Research has been conducted in PT. Perkebunan Nusantara I Pabrik Kelapa Sawit Pulau Tiga workers at Aceh Tamiang, Aceh in 2015 to find out the correlation of nutritional status and calory intake with the work fatigue.The research was analytical with cross-sectional design. The population was 158 workers and sampel was 61 workers that taken by stratified random sampling method.The nutritional status data were gathered by conducting measurement of body mass index with weight and height as the indicator, the calory intake data were gathered by conducted a food recall 24 hours method within 6 workday and the work fatigue data were gathered by conducting interviews by using questionnaires from International Fatigue Research Commite. A statisctic test was used to analyze the correlation between independent variables and dependent variable is the rank spearman correlation test.The result of statistic test with confident interval 95% and confident level 5 % showed that there was significant correlation between the nutritional status and work fatigue at P-value = 0,002. A significant correlation was found between calory intake and work fatigue at P-value 0,0001.It is recommended that workers should conduct dietary managing, increase the food quality and quantity and reduse to consumption instan food.